2023
DOI: 10.1101/2023.05.11.540358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phage activity againstStaphylococcus aureusis impaired in plasma and synovial fluid

Abstract: S. aureus is a pathogen that frequently causes severe morbidity and phage therapy is being discussed as an alternative to antibiotics for the treatment of S. aureus infections. In this in vitro and animal study, we demonstrated that the activity of anti-staphylococcal phages is severely impaired in plasma and synovial fluid. Despite phage replication in these matrices, lysis of the bacteria was slower than phage propagation, and no reduction of the bacterial population was observed. This phage inhibition is du… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…Vibrio cholerae decreases the production of the phage ICP1 receptor (LPS O1-antigen) in response to intestinal bile acids and anaerobiosis, preventing phage predation (47). As well, recent works reported a negative effect of human plasma, particularly fibrinogen and synovial fluid, as well as the complement system, on S. aureus and P. aeruginosa phages infection (40,44,48). With our observations, all these data urge to isolate and select phages in conditions mimicking the "end-user" settings.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Vibrio cholerae decreases the production of the phage ICP1 receptor (LPS O1-antigen) in response to intestinal bile acids and anaerobiosis, preventing phage predation (47). As well, recent works reported a negative effect of human plasma, particularly fibrinogen and synovial fluid, as well as the complement system, on S. aureus and P. aeruginosa phages infection (40,44,48). With our observations, all these data urge to isolate and select phages in conditions mimicking the "end-user" settings.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the host-specificity of the pathogen is also an important criterion. In the case of S. aureus, diluted plasma from human and guinea pig were found to prevent phage infection (40). We found that mice and rabbit sera did not prevent φA25 infection, highlighting the difficulty to use in vivo models other than the NHPs or the human challenge model (25,49) to characterize phage efficacy against S. pyogenes.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations